Legal Protection For Victims Of Mypertamina Barcode Ownership Abuse In The Distribution Of Subsidized Fuel - Ferawati Royani; Sandi Aprianto; Velly Majesti (JURNAL HUKUM SEHASEN, 2026)
This study aims to analyze the legal regulations and forms of criminal liability for perpetrators of misuse of the MyPertamina Barcode in the distribution of subsidized fuel oil (BBM). Since October 2024, the government through PT Pertamina Patra Niaga has implemented a policy of using the MyPertamina barcode as a requirement for purchasing subsidized fuel. However, this policy has created new problems in the form of increased misuse of barcode ownership by irresponsible parties. The research method used is normative juridical with a statutory approach and a case approach. The results of the study indicate that legal regulations regarding the misuse of the MyPertamina barcode are regulated in several laws and regulations, namely Article 378 of the Criminal Code concerning fraud, Article 55 of Law Number 22 of 2001 in conjunction with Article 40 paragraph (9) of Law Number 6 of 2023 concerning the misuse of subsidized fuel, and Articles 65-67 of Law Number 27 of 2022 concerning Personal Data Protection. Criminal liability includes imprisonment and fines, with a maximum penalty of six years and a fine of IDR 60 billion for violations of the Oil and Gas Law, as well as additional penalties in the form of confiscation of evidence. This study recommends strengthening the security system of the MyPertamina application, improving coordination between Pertamina and law enforcement, and improving regulations to impose strict sanctions on perpetrators of abuse.